Meningkatkan Kemampuan Menulis Teks Recount sederhana Pada Siswa Kelas VIIIA SMPN 3 Muara Bungo Melalui Penggunaan Metode Example Non Example, Media Pictures, A Puzzle Words Dan A Lotere Boards. - fatmawati fatmawati (Universitas Muhammadiyah Muara Bungo, 2020)
In accordance with the title of classroom action research, the subjects of the research are class VIIIA students of SMP Negeri 3 Muara Bungo in the even semester of the 2018/2019 school year, some of whom have more abilities and others have medium average abilities. The learning process in the first cycle using the Example Non example model, media pictures, a puzzle words and a lottery boards in making recount text has not been able to improve student learning outcomes, because only 56.25% or 18 students succeeded. However, in cycle II it can reach 81.25% or 26 students who are successful and there is an increase to reach 37.5%. Therefore, it can be said that using 2 cycles in this Classroom Action Research (CAR) to improve student learning outcomes, the average value of students with success criteria is > 5.6.